Metallic Particle Assemblies on Graphene - Gkikas, Manos (Current Organic Chemistry, 2015)
Different approaches to obtain metallic particles on graphene are discussed in this Review article and their applications in catalysis, electrocatalysis and surface enhanced Raman spectroscopy (SERS) are highlighted. Synthetic methods for well-dispersed metallic particles (Au, Ag, Pt, Pd, TiO2 and QDs) on graphene are summarized, and comparisons are made in their utilization in a plethora of applications with pure metallic particles, neat graphene and carbon nanotubes/metallic particles. The importance of utilizing different reductants and stabilizers of metal precursors, as well as the sequential addition of the initial materials (graphene oxide or reduced graphene oxide, metal salts, reductant/stabilizer), are given particular focus, in order to illustrate the strengths and weaknesses in its system. The initial concentrations and volumes of the reagents, the moles of the metal precursor, and the temperature, were found to affect the size and shape of the metal particles and the stability of the graphene/metal hybrids. In this way, the morphology of the inorganic particles on graphene can be tuned for utilization in specific applications, either industrial or biomedical, allowing the development of the next generation materials in catalysis, as sensors, contrast agents and optoelectronics.
Keywords: catalysis